Scalable Functionalization of Optical Fibers Using Atomically Thin Semiconductors - Ngo, Gia Quyet; George, Antony; Klaus Schock, Robin Tristan; Tuniz, Alessandro; Najafidehaghani, Emad; Gan, Ziyang; Geib, Nils C.; Bucher, Tobias; Knopf, Heiko; Saravi, Sina; Neumann, Christof; Luehder, Tilman; et al. (Advanced Materials, 2020)
Atomically thin transition metal dichalcogenides are highly promising for integrated optoelectronic and photonic systems due to their exciton-driven linear and nonlinear interactions with light. Integrating them into optical fibers yields novel opportunities in optical communication, remote sensing, and all-fiber optoelectronics. However, the scalable and reproducible deposition of high-quality monolayers on optical fibers is a challenge. Here, the chemical vapor deposition of monolayer MoS2 and WS2 crystals on the core of microstructured exposed-core optical fibers and their interaction with the fibers’ guided modes are reported. Two distinct application possibilities of 2D-functionalized waveguides to exemplify their potential are demonstrated. First, the excitonic 2D material photoluminescence is simultaneously excited and collected with the fiber modes, opening a novel route to remote sensing. Then it is shown that third-harmonic generation is modified by the highly localized nonlinear polarization of the monolayers, yielding a new avenue to tailor nonlinear optical processes in fibers. It is anticipated that the results may lead to significant advances in optical-fiber-based technologies.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 2D materials; excitonic photoluminescence; integrated photonics; nonlinear optics; transition metal dichalcogenides